Input-Current and Load Voltage Sharing in Input-Parallel Output-Series Connected Boost Half Bridge DC-DC Converter Using Stable Control Scheme - Amir Mahmood Soomro; Shahnawaz Farhan Khahro; Shahnawaz Talpur; Liao Xiaozhong; Farhan Manzoor (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
This paper explores a configuration for boost half bridge DC-DC converters, connected in parallel at the input and series at the output, such that the converters share the input current and load voltage equally. A stable control scheme has been developed to achieve this objective. In order to verify the effectiveness and stability of control scheme, input-parallel output-series (IPOS) connected boost half bridge (BHB) DC-DC Converter has been simulated for the different load conditions such as for fixed load, half load and continuously varying load. The results are found to be satisfactory at each load condition and validate the proposed converter structure. DOI : http://dx.doi.org/10.11591/telkomnika.v12i5.4188